The influence of dark personality and pornography on sexual aggression beliefs - Galán, Manuel; Pineda, David; Rico-Bordera, Pilar; Martínez-Martínez, Ana; Piqueras, Jose A. (Frontiers in Psychology, 2024)
Introduction: Violence against women, particularly sexual violence, poses a significant public health concern. Predispositions toward perpetrating such acts often stem from the acceptance of myths that justify or deny these behaviors. This study aimed to explore how dark personality traits (narcissism, Machiavellianism, psychopathy, and sadism) and pornography consumption relate to the acceptance of these myths. Method: Surveying 598 participants, the research employed Latent Profile Analyses (LPA) to identify distinct population profiles, Additionally, regression analyses were employed to further explore the relationships among variables. Results: Three profiles emerged, showcasing varying degrees of acceptance of sexual aggression myths. The most concerning profile, encompassing 9.2% of participants, displayed the highest alignment with these myths, alongside elevated scores in dark personality traits and pornography consumption. Notwithstanding the three profiles showed significant differences in the acceptance of these myths. Interestingly, the regression analysis highlighted that Machiavellianism stood out as the primary predictor for accepting sexual aggression myths, overshadowing the influence of pornography consumption. Discussion:This emphasizes the role of personality traits in influencing attitudes towards sexual aggression myths. Moreover, implications for tailored prevention strategies, focusing on high-risk profiles, are discussed, highlighting the potential for targeted interventions to address harmful beliefs and behaviors.